(3GdMeGjI GdLfGFjI ddQCi GdYGe ai ehGLgI GdfTQ (B/ s - (3EHQGgje YGOd SdjeGf SfHds; (3eOMJ YHOGdMdje QeVGf (B: s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb (B- (3LGeYI GdbGgQI,s, 2012)
(3jOhQ ehVhY GdHMK Mhd EecGfjI GdJaSjQ GdbVGFj dfUhU LQGFe GdfTQ GdUMaj GdJj JVQ HGdeUdMI GdYGeI ef efXhQ JCKjQgG GdSdHj Ydi GdQCi GdYGe HeG jJab eY eHOC GdTQYjI GdLfGFjI hfWGb Jdc GdfUhU , hPdc dehGLgI ESGAI GdYOjO ef GdeeGQSGJ GdUMajI GdMGdjI dMQjI GdUMGaI HeG jVQ HGdQCi GdYGe hhXGFag GdeNJdaI HGdeLJeY , hJe ESJYQGV Pdc HGdQSGdI NdGd KdGKI CHhGH , JVef GdChd fWGb JLQje JVdjd GdQCi GdYGe HGdfTQ GdUMai (B" (3GdYOhGf Ydi GdMbjbI , hGdKGfj fWGb JLQje JMQjV GdQCi GdYGe Ydi EQJcGH GdLQGFe , hGdKGdK fWGb GdMeGjI GdLfG FjI ddQCi GdYGe HLQGFe GdHZV GdWGFaj hGdfTQ GdNGOT ddMjGA GdYGe , (B. (3hCNjQG GdfJGFL hGdJhUjGJ HGdNGJeI (B.s
(3CWQhMI (B((3OcJhQGg(B)-(3LGeYI GdbGgQI, (B2012.s
. (3HHdjhLQGajG(B: (3UaMGJ (B-244: 258.s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdQCj GdYGes; (3eXGgQ GdJYHjQ Yf GdQCj GdYGes; (3LQGFe eJYdbI HGdQCj GdYGe s; (3LQjeI fTQ GdCNHGQ s; (3GdJMQjV GdYdfj dLeghQ GdQCj GdYGe s; (3GfMjGR GdUMajs; (3GdQCj GdYGes; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- 2012